Biotechnology in Equine Reproduction in The Region of Londrina, Paraná State, Brazil (Research, Society and Development, 2025)
Agricultural Biotechnology, in one of its various fields of activity, seeks to improve techniques for the genetic improvement of animals. This improvement is done through the selection and reproduction of animals with interesting genetic characteristics, seeking to increase productivity, reducing the gap between generations and increase resistance to environmental factors. In horses, the techniques of artificial insemination and embryo transfer have been the most used, historically, for presenting good results. However, some reproduction techniques have obstacles that hinder the advancement of research and, consequently, its dissemination among breeders. In order to know the use of biotechnology in the reproduction of horses in the region of Londrina-PR, we applied a semi-structured questionnaire divided into four sections to breeders. We found that there is a negative correlation between the use of biotechnics and the proportion of stallions in the herd and that the use of semen collection, artificial insemination and embryo transfer prevail, since they can be interconnected, have wide application and generate good results in horses. The breeders declared to invest, on average, R$ 46,500 per year in the execution of these biotechnics. We also realized that, despite the existence of universities that offer the course of veterinary medicine, there is still a shortage of trained professionals in the region. The results allowed us to conclude that, in general, reproduction biotechnology is very widespread among equine breeders in the region of Londrina-PR, although some high-cost techniques have not yet been used.